Protection of Liver as a Remote Organ after Renal Ischemia-Reperfusion Injury by Renal Ischemic Postconditioning - Behjat Seifi; Mehri Kadkhodaee; Atefeh Najafi; Atefeh Mahmoudi (International Journal of Nephrology)
This study was designed to investigate the protective effects of local renal ischemic postconditioning (POC) on liver damage after renal ischemia-reperfusion (IR) injury. Male rats were divided into three groups  (n=8). They underwent a right nephrectomy before induction of 45 minutes of left kidney ischemia or sham operation. POC was performed by four cycles of 10 seconds of ischemia and 10 seconds of reperfusion just at the beginning of 24 hours of reperfusion. Then blood and liver samples were collected to measure serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and liver oxidative stress parameters including superoxide dismutase (SOD) activity and malondialdehyde (MDA) level. Renal IR caused a significant increase in liver functional indices as demonstrated by increased serum AST and ALT compared to sham group. These parameters reduced significantly in POC group compared to IR group. Liver MDA levels increased and SOD activity decreased in IR group compared to sham group. Induction of POC reduced the elevated liver MDA levels and increased the reduced liver SOD activity. These results revealed that renal IR injury causes liver damage as a remote organ and POC protects liver from renal IR injury by a modification in the hepatic oxidative stress status.